Synthesis, Formulation and Characterization of Immunotherapeutic Glycosylated Dendrimer/cGAMP Complexes for CD206 Targeted Delivery to M2 Macrophages in Cold Tumors - Marija Petrovic; Alexandre Porcello; Stoyan Tankov; Oliwia Majchrzak; Martin Kiening; Annick Clara Laingoniaina; Tayeb Jbilou; Paul R. Walker; Gerrit Borchard; Olivier Jordan (MDPI AG, 2022)
Anti-tumor responses can be achieved via the stimulation of the immune system, a therapeutic approach called cancer immunotherapy. Many solid tumor types are characterized by the presence of immune-suppressive tumor-associated macrophage (TAMs) cells within the tumor microenvironment (TME). Moreover, TAM infiltration is strongly associated with poor survival in solid cancer patients and hence a low responsiveness to cancer immunotherapy. Therefore, 2'3' Cyclic GMP-AMP (2'3' cGAMP) was employed for its ability to shift macrophages from pro-tumoral M2-like macrophages (TAM) to anti-tumoral M1. However, cGAMP transfection within macrophages is limited by the molecule's negative charge, poor stability and lack of targeting. To circumvent these barriers, we designed nanocarriers based on poly(amidoamine) dendrimers (PAMAM) grafted with D-glucuronic acid (Glu) for M2 mannose-mediated endocytosis. Two carriers were synthesized based on different dendrimers and complexed with cGAMP at different ratios. Orthogonal techniques were employed for synthesis (NMR, ninhydrin, and gravimetry), size (DLS, NTA, and AF4-DLS), charge (DLS and NTA), complexation (HPLC-UV and AF4-UV) and biocompatibility and toxicity (primary cells and hen egg chorioallantoic membrane model) evaluations in order to evaluate the best cGAMP carrier. The best formulation was selected for its low toxicity, biocompatibility, monodispersed distribution, affinity towards CD206 and ability to increase M1 (STAT1 and NOS2) and decrease M2 marker (MRC1) expression in macrophages.